PERSEPSI SANTRI TERHADAP METODE PEMBELAJARAN KITAB KUNING SERTA IMPLIKASINYA PADA PEMAHAMAN KEAGAMAAN : STUDI KASUS DI PONDOK PESANTREN NURUL ISLAM DESA MANUNGGAL JAYA TENGGARONG SEBRANG - Sofiya Azizah Al Zahro; Firawati; Alifah Nurindah; Mubarak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines students’ perceptions of the yellow book (kitab kuning) learning methods and their implications for religious understanding at Nurul Islam Islamic Boarding School, Manunggal Jaya Village, Tenggarong Seberang District, Kutai Kartanegara Regency. The research was motivated by the varying levels of students’ understanding of kitab kuning materials despite the implementation of various learning methods in the pesantren. The purpose of this study was to analyze students’ perceptions of the learning methods used and to identify their implications for students’ religious understanding. This research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving teachers and students as research informants. The collected data were analyzed using the interactive model of Miles and Huberman, including data reduction, data presentation, and conclusion drawing. The findings indicate that students generally have positive perceptions of the kitab kuning learning methods implemented at the pesantren. The gradual learning process, opportunities for discussion, and direct guidance from teachers help students understand the material more effectively despite difficulties related to language and content comprehension. Furthermore, the learning methods contribute positively to students’ religious understanding by enhancing their knowledge of Islamic teachings and encouraging the application of religious values in daily life. The study concludes that the kitab kuning learning methods applied at Nurul Islam Islamic Boarding School support both religious comprehension and character development among students.